Tunnel disease rapid repair water-based polymer mortar and its preparation method and application

CN122897647APending Publication Date: 2026-10-13济南轨道交通集团建设投资有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611034544.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

同时,普通水泥基砂浆整体脆性较大,抗折韧性和裂缝桥联能力有限,在长期循环动载和环境侵蚀作用下,修复层内部微裂纹容易持续扩展,从而降低修复效果和使用寿命

Benefits of technology

本发明通过采用经球磨和高温活化处理的黄金尾矿粉作为胶凝体系的重要组成部分,提高了黄金尾矿中硅铝组分的潜在反应活性,使其能够在水泥水化形成的碱性环境中参与二次反应,并与水泥、矿渣和偏高岭土共同形成水化硅酸钙凝胶、水化铝硅酸钙凝胶等水化产物,从而改善砂浆内部结构,提高材料强度和致密性,在保证修复材料性能的同时实现了黄金尾矿的资源化利用,有利于减少工业固体废弃物堆存压力,具有较好的环境效益和工程应用价值。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application provides a kind of tunnel disease rapid repair water-based polymer mortar and its preparation method and application, it is related to tunnel engineering repair material technical field.The tunnel disease rapid repair water-based polymer mortar of the application includes the gold tailings powder treated by ball milling, high-temperature activation, fast hard sulphoaluminate cement, slag, metakaolin, nanometer silicon dioxide, water-based polyurethane cementing material, silane coupling agent, water reducing agent, fiber, quartz sand, coagulant, the water-binder ratio of the slurry is 0.35~0.45;The specific surface area of the gold tailings powder is greater than or equal to 600 m 2 / kg, D 50 ≤8 μm, SiO2 content is greater than or equal to 65%.The application realizes the rapid setting and hardening of tunnel disease repair material, early strength improvement, interface bonding enhancement, crack toughness improvement and permeability resistance durability improvement, and has good application prospect in the operation tunnel disease rapid repair and high value utilization of mine solid waste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of tunnel engineering repair materials technology, and in particular to a water-based polymer mortar for rapid repair of tunnel defects, its preparation method, and its application. Background Technology

[0002] As the service life of highway, railway, and urban rail transit tunnels increases, tunnel lining structures are susceptible to damage from a combination of factors, including train vibration, alternating wind pressure, water leakage, freeze-thaw cycles, and environmental erosion. This damage can lead to issues such as surface concrete spalling, honeycomb-like surface defects, localized spalling, non-structural cracks, and hollowing and detachment of repair layers. These defects not only affect the durability and service safety of the tunnel structure but also often require rapid repair during limited maintenance windows in operating tunnels. Therefore, higher requirements are placed on the setting and hardening speed, early strength, substrate adhesion, crack resistance, and adaptability to humid environments of the repair materials.

[0003] While ordinary cement-based mortar, commonly used in tunnel repair, offers advantages such as low cost and ease of application, its relatively slow setting and hardening rate, coupled with insufficient early strength development, makes it difficult to establish a stable load-bearing structure quickly. When the tunnel resumes operation before the repair material has fully hardened, the repair layer is prone to cracking, loosening, or secondary spalling under the vibration loads generated by train operation and alternating wind pressure. Furthermore, ordinary cement-based mortar exhibits high overall brittleness, limited flexural toughness, and limited crack bridging capacity. Under long-term cyclic dynamic loading and environmental erosion, microcracks within the repair layer are prone to continuous propagation, thereby reducing the repair effectiveness and service life.

[0004] Furthermore, tunnel lining defects are typically found in damp or even seeping environments, with existing concrete substrates exhibiting high moisture content and complex surface conditions. Ordinary cement-based repair materials have limited interfacial adhesion to damp surfaces, easily leading to interfacial defects between the repair layer and the original concrete. These defects can further develop into hollow areas, peeling, or detachment during subsequent service. While some projects utilize chemical materials such as epoxy resin, polyurethane, and acrylamide for repair or grouting, these materials offer some effectiveness in bonding or water-stopping. However, they generally suffer from high costs, significant environmental impact on durability, limited ability to deform in tandem with inorganic substrates, and environmental or construction safety risks associated with some materials. Consequently, they struggle to simultaneously achieve economic efficiency, safety, mechanical properties, and long-term stability in large-area repair scenarios.

[0005] On the other hand, mining solid waste emissions, such as gold tailings, are substantial. Long-term stockpiling not only occupies land resources but also poses challenges to dust, leaching, and environmental remediation. Using gold tailings in building materials is an important direction for realizing the resource utilization of solid waste. However, the silica and aluminum components in undisturbed gold tailings are mostly stable mineral phases with low reactivity. If used only as inert fillers or ordinary fine aggregates, their contribution to the early strength, density, and durability of repair materials is limited, making it difficult to meet the comprehensive requirements of rapid setting, early strength, strong adhesion, and impermeability durability for tunnel rapid repair materials. How to improve the reactivity of gold tailings through appropriate treatment and synergistically design it with rapid-hardening cementitious materials, mineral admixtures, polymer-modified components, and fiber-reinforced components is a key issue that needs to be addressed in developing green, high-performance tunnel rapid repair materials.

[0006] Therefore, it is necessary to provide a water-based polymer mortar for rapid repair of tunnel defects, its preparation method and application, so that it can meet the requirements of short-term construction and early load-bearing capacity, while also having good bonding performance, crack resistance, impermeability and durability and solid waste resource utilization effect, so as to adapt to the complex engineering conditions of operating tunnels such as moisture, vibration and rapid emergency repair. Summary of the Invention

[0007] In view of this, the present invention provides a water-based polymer mortar for rapid repair of tunnel defects, its preparation method, and its application. The present invention achieves rapid setting and hardening, early strength enhancement, enhanced interfacial bonding, improved crack resistance and toughness, and improved impermeability and durability of the tunnel defect repair material through ball milling and high-temperature activation of gold tailings, followed by compounding with rapid-hardening sulfoaluminate cement, slag, metakaolin, nano-silica, water-based polyurethane, silane coupling agent, fiber, and admixtures. It has promising application prospects in the rapid repair of defects in operating tunnels and the high-value utilization of mine solid waste.

[0008] The first aspect of this invention provides a water-based polymer mortar for rapid repair of tunnel defects, comprising: The mixture comprises: 35-60 parts of gold tailings powder that has undergone ball milling and high-temperature activation treatment; 20-35 parts of rapid-hardening sulfoaluminate cement; 10-20 parts of slag; 5-15 parts of metakaolin; 0.5-2 parts of nano-silica; 3%-8% of the mass of the cementitious material based on the total mass of the emulsion; 0.5%-1.5% of the mass of the waterborne polyurethane; 0.2%-0.5% of the mass of the cementitious material based on the water-reducing agent; 0.05%-0.2% of the mass of the cementitious material based on the fiber; 80-150 parts of quartz sand; 0.3% of the mass of the cementitious material based on the coagulating agent; and water to achieve a water-cement ratio of 0.35-0.45. The cementitious material is the sum of gold tailings powder, cement, slag, metakaolin, and nano-silica. The specific surface area of ​​the gold tailings powder is ≥600 m².2 / kg, D 50 ≤8 μm, SiO2 content ≥65%.

[0009] Preferably, the slag is S95 grade granulated blast furnace slag; the metakaolin is highly reactive metakaolin, calcined at 600-900℃, with an Al2O3 content of 40%; and the nano-silica has an average particle size of 10-50 nm and a specific surface area of ​​100-300 m². 2 / g; the waterborne polyurethane is an anionic waterborne polyurethane emulsion with a solid content of 40%~50% and a viscosity of 50~300 mPa·s; the silane coupling agent is an aminosilane coupling agent and / or an epoxysilane coupling agent, more preferably γ-aminopropyltriethoxysilane (KH550); the water-reducing agent is a polycarboxylate-based high-performance water-reducing agent with a water reduction rate ≥25%; the fiber is PVA fiber or polypropylene fiber, more preferably PVA fiber, with a length of 6~12 mm; the quartz sand is 70~120 mesh graded quartz sand, and the quartz sand is 0.8~1.5 times the mass of the cementitious material, more preferably 1.0 times; the coagulant is at least one of inorganic lithium salt, inorganic sodium salt, and organic alcohol amine coagulant, more preferably sodium sulfate.

[0010] A second aspect of this invention provides a method for preparing the aforementioned water-based polymer mortar for rapid repair of tunnel defects, comprising the following steps: S1. The gold tailings are ball-milled, screened and classified, and then subjected to high-temperature calcination activation treatment to obtain high-temperature activated gold tailings powder. S2. The gold tailings powder, rapid hardening sulfoaluminate cement, slag, metakaolin, nano silica, quartz sand, water-reducing agent and accelerator treated at high temperature are dry-mixed in proportion to disperse them evenly to obtain a dry mixture. S3. Add a portion of the silane coupling agent and water to the dry mixture and stir to form a uniform inorganic slurry 1. S4. Mix the waterborne polyurethane with the remaining silane coupling agent and stir until homogeneous to form a uniform organic slurry 2. S5. Add the organic slurry 2 to the inorganic slurry 1 and mix them evenly under high-speed stirring to form an organic-inorganic composite mortar. S6. Add the fiber to the organic-inorganic composite mortar, and disperse the fiber evenly under low-speed stirring conditions. Stir until there are no bundled fibers on the surface of the mortar, so that the fiber is evenly dispersed and does not agglomerate, to obtain the water-based polymer mortar for rapid repair of tunnel defects.

[0011] Preferably, in step S1, the ball mill speed is 400 r / min, the ball milling time is 30 min, the sieving uses a 0.075 mm sieve, the heating rate of the high-temperature calcination is 5℃ / min, the high-temperature calcination temperature is 650℃, the holding time is 2 h, and after calcination, the furnace is cooled to room temperature.

[0012] Preferably, in step S3, the stirring is first performed at a low speed of 100-200 r / min for 30 s, and then at a high speed of 250-500 r / min for 3 min, until the slurry is uniform, viscous and has a certain gloss, without obvious agglomeration or bleeding.

[0013] Preferably, in step S4, the stirring of the waterborne polyurethane and the silane coupling agent is carried out in a separate premix tank; the mass ratio of the partial silane coupling agent to the remaining silane coupling agent is 1:(0.5~2), more preferably 1:1.

[0014] Preferably, in step S5, the high-speed stirring speed is 250-500 r / min, the time is 3-6 min, and the stirring is carried out until the slurry is uniform, free of cement lumps and has good fluidity.

[0015] Preferably, in step S6, the low-speed stirring speed is 100~200 r / min, and the stirring is continued until there are no bundled fibers on the surface of the slurry, so that the fibers are evenly dispersed and do not agglomerate.

[0016] The third aspect of this invention provides the application of the aforementioned water-based polymer mortar for rapid repair of tunnel defects in tunnel defect repair projects.

[0017] Compared with the prior art, the beneficial technical effects of the present invention are as follows: This invention utilizes ball-milled and high-temperature activated gold tailings powder as a crucial component of the cementitious system. This enhances the potential reactivity of the silica-alumina components in the gold tailings, enabling them to participate in secondary reactions within the alkaline environment formed during cement hydration. The tailings then combine with cement, slag, and metakaolin to form hydration products such as hydrated calcium silicate gel and hydrated calcium aluminosilicate gel. This improves the internal structure of the mortar, increasing its strength and density. While ensuring the performance of the repair material, this invention achieves the resource utilization of gold tailings, reducing the pressure of industrial solid waste accumulation and demonstrating significant environmental benefits and engineering application value.

[0018] This invention utilizes rapid-hardening sulfoaluminate cement and an accelerator to construct a fast-hardening cementitious system. This allows the mortar to achieve early structural strength within a short time after mixing, meeting the engineering requirements of short maintenance windows in operating tunnels and the need for rapid restoration of traffic after construction. Compared to ordinary silicate cement repair mortar, the material of this invention sets and hardens faster, and has higher early compressive and flexural strengths. This helps reduce the risk of loosening, damage, or detachment of the repair layer during the early service stages due to vibration loads and alternating wind pressure.

[0019] This invention introduces slag and metakaolin to form a multi-component synergistic reaction system with activated gold tailings powder and cement hydration products. This system facilitates the continuous generation of gel products and refines the pore structure, thereby improving the later-stage mechanical properties and volume stability of the mortar. The active aluminosilicate component in the metakaolin promotes the formation of the aluminosilicate gel phase in the system, while the slag participates in potential hydraulic reactions. The synergistic effect of these two components with the activated tailings powder allows the mortar to maintain good later-stage strength development even after rapid early hardening.

[0020] This invention introduces nano-silica, utilizing its nano-filling effect and nucleation promoting function to improve the microporous structure of the cementitious system, promote the generation and deposition of early hydration products, and reduce the connectivity of capillaries within the hardened mortar. Therefore, the material of this invention not only improves early strength and structural density but also enhances its impermeability and water resistance in humid environments, making it suitable for surface repair of damp surfaces and leaky environments in tunnel linings.

[0021] This invention introduces waterborne polyurethane to form a flexible polymer phase during the hardening process of inorganic cementitious materials. This flexible phase can distribute between inorganic hydration products and in weak areas such as pores and microcracks, thereby improving the problems of high brittleness and rapid crack propagation in single inorganic mortars. The addition of waterborne polyurethane helps improve the mortar's flexural strength, deformation coordination, and crack bridging ability, giving the repair layer better crack resistance and spalling resistance under train vibration and alternating wind pressure.

[0022] This invention improves the interfacial compatibility and bonding state between the organic phase of waterborne polyurethane and the inorganic phase of cement-based materials by introducing a silane coupling agent, thereby reducing interfacial defects in the organic-inorganic composite system. The combined use of the silane coupling agent and waterborne polyurethane enhances the overall stability of the composite mortar and its bond strength to existing concrete substrates, thus reducing the risk of interfacial debonding, hollowing, and detachment of the repair layer under humid or vibrating conditions.

[0023] This invention incorporates fibers to form a dispersed reinforcing structure within the mortar, which bridges, inhibits, and toughens microcracks, delaying crack propagation and improving the crack resistance and integrity of the repair layer. The fiber reinforcement, combined with the flexible modification by water-based polyurethane, gives the material of this invention better toughness and service stability than ordinary cement-based mortar, making it more suitable for tunnel lining repair applications subjected to long-term vibration and alternating loads.

[0024] This invention employs a stepwise preparation and compound mixing process of inorganic and organic slurries, which improves the dispersion uniformity among waterborne polyurethane, silane coupling agents, and inorganic cementitious components. This reduces problems such as polymer demulsification, localized agglomeration, or fiber clumping, ensuring the mortar has good workability and component uniformity. The preparation method has clear process steps, readily available raw materials, and is suitable for rapid on-site mixing and tunnel repair applications.

[0025] The water-based polymer mortar for rapid repair of tunnel defects provided by this invention can set and harden in a short time, achieving high early strength. It also possesses good bonding properties, crack resistance, water resistance, and impermeability. It can be used for the rapid repair of defects such as surface spalling, honeycomb pitting, localized spalling, and non-structural cracks in tunnel lining. This material meets the needs of rapid repair of operational tunnels and the resource utilization of gold tailings, demonstrating significant engineering application value and promising prospects for widespread application. Detailed Implementation

[0026] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0027] Unless otherwise specified, all experiments were repeated three times, and the results are expressed as averages.

[0028] Example 1: A method for preparing a water-based polymer mortar for rapid repair of tunnel defects, comprising the following steps: S1. Add an appropriate amount of raw gold tailings into a ball mill and ball mill at 400 r / min for 30 min to obtain gold tailings powder. Add the ball-milled raw gold tailings powder into a box-type muffle furnace and calcine and activate it at 650℃. S2. Weigh the gold tailings powder after high-temperature activation (specific surface area 3.3 m²). 2 / g,D 50 45 parts of rapid-hardening sulfoaluminate cement (7 μm, SiO2 content 65%), 30 parts of blast furnace slag, 15 parts of metakaolin, and 1 part of nano-silica (specific surface area 200 m²).2 / g), waterborne polyurethane is 5% of the mass of cementitious material (5 parts in this example, based on the total mass of the emulsion), PVA fiber is 0.1% of the mass of cementitious material (0.1 parts in this example), silane coupling agent is 1% of waterborne polyurethane (0.05 parts in this example), polycarboxylate superplasticizer is 0.35% of the mass of cementitious material (0.35 parts in this example), quartz sand is 100 parts, accelerator is 0.3 parts, and the water-cement ratio is controlled at 0.4. The weighed high-temperature activated gold tailings powder, rapid hardening sulfoaluminate cement, slag, metakaolin, nano silica, quartz sand, superplasticizer and accelerator are mixed evenly in dry powder state to obtain dry mixture; S3. Add 0.025 parts of silane coupling agent and an appropriate amount of water to the dry mixture. First, stir at a low speed of 150 r / min for 30 s, and then stir at a high speed of 375 r / min for 3 min to form a uniform inorganic slurry 1. S4. Mix 5 parts of waterborne polyurethane with 0.025 parts of silane coupling agent, stir and mix evenly to form a uniform organic slurry 2. S5. Add organic slurry 2 to inorganic slurry 1 and mix them evenly at high speed for 5 minutes at 375 r / min to form organic-inorganic composite modified slurry. S6. Add 0.1 parts of PVA fiber to the organic-inorganic composite modified slurry and stir at low speed at 150 r / min until there are no bundled fibers on the surface of the slurry, so that the fibers are evenly dispersed and do not agglomerate, to obtain a rapid repair water-based polymer mortar.

[0029] Example 2 The difference from Example 1 is as follows: In step S2, 60 parts of gold tailings powder after high-temperature activation, 20 parts of rapid-hardening sulfoaluminate cement, 12 parts of slag, 7 parts of metakaolin, 1 part of nano-silica, 5% of the mass of waterborne polyurethane (5 parts in this example), 0.1% of the mass of PVA fiber (0.1 parts in this example), 1% of the waterborne polyurethane silane coupling agent (0.05 parts in this example), 0.35% of the mass of polycarboxylate superplasticizer (0.35 parts in this example), 100 parts of quartz sand, 0.3 parts of coagulating accelerator, and the water-cement ratio is controlled at 0.4; the rest of the preparation method is the same as in Example 1.

[0030] Example 3 The difference from Example 1 is as follows: In step S2, 45 parts of gold tailings powder after high-temperature activation, 30 parts of rapid-hardening sulfoaluminate cement, 12 parts of slag, 11 parts of metakaolin, 2 parts of nano-silica, 5% of the mass of waterborne polyurethane (5 parts in this example), 0.1% of the mass of PVA fiber (0.1 parts in this example), 1% of the waterborne polyurethane silane coupling agent (0.05 parts in this example), 0.35% of the mass of polycarboxylate superplasticizer (0.35 parts in this example), 100 parts of quartz sand, 0.3 parts of coagulating accelerator, and the water-cement ratio is controlled at 0.4; the rest of the preparation method is the same as in Example 1.

[0031] Example 4 The difference from Example 1 is as follows: In step S2, 40 parts of gold tailings powder after high-temperature activation, 35 parts of rapid-hardening sulfoaluminate cement, 15 parts of slag, 9 parts of metakaolin, 1 part of nano-silica, 5% of the mass of waterborne polyurethane (5 parts in this example), 0.1% of the mass of PVA fiber (0.1 parts in this example), 1% of the waterborne polyurethane silane coupling agent (0.05 parts in this example), 0.35% of the mass of polycarboxylate superplasticizer (0.35 parts in this example), 100 parts of quartz sand, 0.3 parts of coagulating accelerator, and the water-cement ratio is controlled at 0.4; the rest of the preparation method is the same as in Example 1.

[0032] Comparative Example 1 The difference from Example 1 is that waterborne polyurethane and silane coupling agent were not added; in step S2, 45 parts of gold tailings powder after high-temperature activation, 30 parts of rapid-hardening sulfoaluminate cement, 15 parts of slag, 9 parts of metakaolin, 1 part of nano silica, 0.1% of the mass of PVA fiber as cementitious material, 0.35% of the mass of polycarboxylate superplasticizer as cementitious material (0.35 parts in this comparative example), 100 parts of quartz sand, 0.3 parts of accelerator, and the water-cement ratio was controlled at 0.4; the operations related to waterborne polyurethane and silane coupling agent in steps S3 to S5 of Example 1 were omitted in the preparation method, and the rest were the same as in Example 1.

[0033] Comparative Example 2 The difference from Example 1 is that: no high-temperature activated gold tailings powder was added; instead, undisturbed gold tailings powder that had been ball-milled to the same fineness but had not been activated by high-temperature calcination was added; high-temperature calcination activation treatment was not performed in step S1; in step S2, 45 parts of undisturbed gold tailings powder, 30 parts of rapid-hardening sulfoaluminate cement, 15 parts of slag, 9 parts of metakaolin, 1 part of nano-silica, 5% of the mass of waterborne polyurethane (5 parts in this comparative example), 0.1% of the mass of PVA fiber (0.1 parts in this comparative example), 1% of the waterborne polyurethane (0.05 parts in this comparative example), 0.35% of the mass of polycarboxylate superplasticizer (0.35 parts in this comparative example), 100 parts of quartz sand, 0.3 parts of coagulating accelerator, and the water-cement ratio was controlled at 0.4; the rest of the preparation method was the same as in Example 1.

[0034] Comparative Example 3 The difference from Example 1 is that nano-silica was not added, and the amount was made up with an equal mass of quartz powder. The remaining components, dosages and preparation methods are the same as in Example 1.

[0035] Comparative Example 4 The difference from Example 1 is that the rapid-hardening sulfoaluminate cement is replaced with ordinary silicate cement (PO 42.5); in step S2, 45 parts of gold tailings powder after high-temperature activation, 30 parts of ordinary silicate cement, 15 parts of slag, 9 parts of metakaolin, 1 part of nano silica, 5% of waterborne polyurethane by mass of cementitious materials (5 parts in this comparative example), 0.1% of PVA fiber by mass of cementitious materials (0.1 parts in this comparative example), 1% of silane coupling agent by waterborne polyurethane (0.05 parts in this comparative example), 0.35% of polycarboxylate superplasticizer by mass of cementitious materials (0.35 parts in this comparative example), 100 parts of quartz sand, 0.3 parts of accelerator, and the water-cement ratio is controlled at 0.4; the rest of the preparation method is the same as in Example 1.

[0036] Test Example 1 The materials prepared in Specific Examples 1-4 and Comparative Examples 1-4 were subjected to 28-day flexural and compressive strength tests, setting time tests, flowability tests, bond strength tests, water resistance tests, and permeability coefficient tests.

[0037] The setting time test of the rapid repair water-based polymer mortar was conducted according to the "Standard Consistency Water Requirement, Setting Time and Soundness Test Methods for Cement" (GB / T 1346-2024); the fluidity test was conducted according to the "Cement Mortar Flowability Test Method" (GB / T2419-2005); the compressive and flexural strength tests were conducted according to the "Cement Mortar Strength Test Method (ISO Method)" (GB / T 17671-2021), with natural curing at room temperature for 28 days, and the 28-day compressive and flexural strengths were measured; the bond strength test was conducted according to the "Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019), using a pull-out test method to test the bond between the molded mortar and the existing concrete substrate. The concrete substrate was ground, cleaned, and moistened to a surface-dry state, with a bonding area of ​​40 mm × 40 mm, and the pull-out loading rate was controlled at 0.05. MPa / s, record the failure load and calculate the bond strength; water resistance testing is a series of experimental methods to evaluate the ability of a material to retain its physical, chemical, electrical, or appearance properties after contact with moisture or a humid environment. There is usually no unified standard; it is generally expressed using the water resistance coefficient (M). In the field of engineering materials, the water resistance coefficient is often referred to as the softening coefficient, as shown in the following formula: In the formula: Rw is the compressive strength of the material in the water-saturated state; Ra is the compressive strength in the natural drying environment.

[0038] The permeability coefficient test was conducted according to the "Standard for Test Methods of Long-Term Performance and Durability of Concrete" (GB / T 50082-2024), with appropriate adjustments made based on the characteristics of the grout material. The variable head method was used to test the permeability performance of the samples. Before testing, the samples were fully saturated with water and placed in a permeameter. Under a certain head difference, the change in head over time was recorded, and the permeability coefficient was calculated using the formula shown below. Each test was repeated three times, and the average value was taken as the final result.

[0039]

[0040] In the formula: k is the permeability coefficient (m / s); a is the cross-sectional area of ​​the piezometer (cm²). 2 A is the cross-sectional area of ​​the sample (cm²) 2 L is the sample height (cm); t is the time (s); h1 and h2 are the initial head and the final head (cm), respectively.

[0041] Table 1 Performance Indicators of Rapid Repair Waterborne Polymer Mortar ; As shown in Table 1, the initial setting time of Examples 1-4 was 15-26 min, and the final setting time was 24-42 min, both significantly shorter than that of ordinary cement-based repair materials. This indicates that the system has excellent rapid setting ability and can meet the needs of short-term emergency repair construction during tunnel "window periods". Among them, Example 4, due to the increased amount of rapid-hardening sulfoaluminate cement, had its initial setting time shortened to 15 min and its final setting time to 24 min, respectively. This indicates that rapid-hardening sulfoaluminate cement can quickly generate a large number of ettringite (AFt) crystals, accelerate the formation of the slurry skeleton structure, and thus significantly improve the setting and hardening speed. In Example 3, due to the increased content of nano-silica and metakaolin, its setting time was also shortened. This is because nano-silica has a high specific surface area and can play a nucleation induction role, promoting the precipitation of early hydration products. At the same time, the active Al2O3 in metakaolin participates in the reaction, further promoting the formation of AFt and gel phase. The flowability results showed that the flowability of Examples 1-4 remained between 185 and 215 mm, indicating that the system maintained good workability and finishing performance while retaining rapid setting characteristics. Example 2 had the highest flowability, reaching 215 mm, which may be related to improved particle size distribution, reduced cement content, and a lower early hydration reaction rate, thus improving the particle size distribution of the paste and reducing interparticle frictional resistance. In Example 3, due to the increased content of nano-silica, its ultra-high specific surface area adsorbed some free water, causing the flowability to decrease to 185 mm, but still within a reasonable workability range. In contrast, Comparative Example 2, using unactivated undisturbed gold tailings, achieved a flowability of 230 mm, but the setting time was significantly prolonged, indicating that while the undisturbed tailings had a certain filling effect, they lacked activity and could not effectively participate in the early hydration reaction, leading to a decrease in the overall reaction rate of the system. In Comparative Example 4, after replacing rapid-hardening sulfoaluminate cement with ordinary silicate cement, the initial setting time and final setting time were extended to 120 min and 243 min, respectively, which were much higher than those in the Example Group. This indicates that ordinary silicate cement is difficult to meet the requirements of tunnel rapid repair materials for short-time hardening, and further verifies the key role of rapid-hardening sulfoaluminate cement in this invention.

[0042] For the 2-hour early strength test, the specimens were cured in a molded environment at 20℃±2℃ and relative humidity ≥95% for 2 hours. They were then demolded and immediately subjected to flexural and compressive strength tests, with the loading rate conforming to GB / T 17671-2021. For the 28-day strength test, the specimens were naturally cured at room temperature for 28 days before their compressive and flexural strengths were tested. In the bond strength test, the concrete substrate was kept moist but surface-dry to simulate the damp lining substrate of a tunnel.

[0043] Table 2 Mechanical Properties of Rapid Repair Waterborne Polymer Mortar ; As shown in Table 2, the 2-hour compressive strength test results indicate that the materials in all example groups can develop high early strength in a short time. Specifically, the 2-hour compressive strengths of Examples 3 and 4 reach 24.0 MPa and 26.5 MPa, respectively, demonstrating that the materials can quickly establish load-bearing capacity under short-term construction conditions during tunnel "skylight periods," meeting the requirements for rapid traffic opening. Table 2 also shows that Example 3 exhibits the best performance in the 28-day strength test, with a 28-day flexural strength of 10.5 MPa, a 28-day compressive strength of 51 MPa, and a bond strength of 3.5 MPa. This is mainly attributed to the synergistic effect of nano-silica and metakaolin: on the one hand, nano-silica can fill the micropores in the slurry through the nano-filling effect, improving the structural density; on the other hand, nano-silica can promote the nucleation and deposition of early hydration products, and participate in the cementation reaction together with the active aluminum-silica components in metakaolin, promoting the formation of AFt and C-(A)-SH gel phases, resulting in a more dense and stable three-dimensional cementitious network structure inside the slurry. Therefore, Example 3 has the best overall mechanical properties. Although Example 2 increased the gold tailings content, its 28-day compressive strength decreased to 38.2 MPa due to the corresponding reduction in cement content. This indicates that when the tailings replacement rate is too high, the effective cementitious components in the system decrease, which will have a certain impact on the later strength. However, its strength is still significantly higher than that of Comparative Example 2, indicating that the gold tailings activated at high temperature have good potential pozzolanic activity and can participate in the secondary hydration reaction in an alkaline environment, improving the overall strength of the material. Comparative Example 1, without the addition of waterborne polyurethane and silane coupling agent, exhibited a flexural strength of only 5.5 MPa and a bonding strength of only 0.8 MPa, significantly lower than the Example group. This indicates that the single inorganic cementitious system is brittle and lacks sufficient interfacial bonding ability. In contrast, waterborne polyurethane forms a flexible polymer film structure during the hardening process, effectively bridging microcracks and improving the system's toughness. The silane coupling agent, on the other hand, can form chemical bonds between the organic and inorganic phases, enhancing the interfacial bonding strength. Therefore, the synergistic effect of the two significantly improves the material's crack resistance and bonding performance. In Comparative Example 2, due to the use of unactivated undisturbed gold tailings, its 28-day compressive strength was only 32.5 MPa, significantly lower than Example 1. This is because SiO2 and Al2O3 in the undisturbed gold tailings mainly exist in stable crystalline forms with low activity, making it difficult to effectively participate in the volcanic ash reaction. However, after activation at 650℃, the tailings' crystalline structure is destroyed, increasing the content of amorphous phases and thus enhancing its reactivity. This promotes the formation of hydration products such as AFt and C-(A)-SH, thereby increasing the material's strength.

[0044] Table 3 Durability Performance Indicators of Rapid Repair Waterborne Polymer Mortar ; As shown in Table 3, all example groups exhibited high water resistance coefficients and low permeability coefficients. Example 3, in particular, achieved a water resistance coefficient of 0.96 and a permeability coefficient of only 1.8 × 10⁻⁶. -12 The permeability coefficient (m / s) indicates that it maintains high structural stability and excellent impermeability even under long-term humid conditions. This is mainly due to the multi-scale dense structure jointly constructed by high-temperature activated gold tailings, slag, metakaolin, and nano-silica. The large amount of gel products generated continuously fills the capillary channels, gradually transforming the pore structure from harmful capillaries to gel pores, thereby reducing pore connectivity and blocking water permeation paths. Simultaneously, the waterborne polyurethane forms a continuous flexible membrane structure within the slurry, providing a certain sealing effect on cracks; the silane coupling agent enhances the stability of the organic-inorganic interface. Therefore, the overall impermeability of the example group is significantly better than that of the comparative group. Comparative Example 1, without the addition of a polymer system, achieved a permeability coefficient of 12.0 × 10⁻⁶. -12 The permeability coefficient of the single inorganic system is m / s, indicating strong pore connectivity and susceptibility to water seepage in humid environments. In Comparative Example 2, due to insufficient activity of the undisturbed tailings, a dense gel structure could not be effectively formed, further increasing its permeability coefficient to 18.5 × 10⁻⁶ m / s. -12 The m / s indicates that high-temperature activation treatment plays an important role in improving the system's density and impermeability.

[0045] Comparative Example 5 The difference from Example 1 is that: instead of adding 45 parts of gold tailings powder activated at high temperature, gold tailings are used as sand aggregate. The particle size of the gold tailings sand aggregate is 70-120 mesh, and the amount is 45 parts. Correspondingly, the composition of the cementitious material is adjusted to 30 parts of rapid-hardening sulfoaluminate cement, 15 parts of slag, 9 parts of metakaolin, and 1 part of nano silica. The amount of waterborne polyurethane, silane coupling agent, water-reducing agent, PVA fiber, and water is calculated according to the adjusted cementitious material mass. The rest of the preparation method is the same as in Example 1.

[0046] The comparative example was tested and found to have an initial setting time of 30 min, a final setting time of 48 min, a flowability of 205 mm, a 2-hour flexural strength of 1.5 MPa, a 2-hour compressive strength of 7.8 MPa, a 28-day flexural strength of 5.8 MPa, a 28-day compressive strength of 30.5 MPa, a bond strength of 1.7 MPa, a water resistance coefficient of 0.83, and a permeability coefficient of 15.5 × 10⁻⁶. -12 m / s.

[0047] Comparative Example 6 The difference from Example 1 is that 5 parts of waterborne polyurethane are added, and no silane coupling agent is added; the addition of silane coupling agent as in Example 1 is omitted during preparation, and the remaining components, dosages and preparation methods are the same as in Example 1.

[0048] The comparative example was tested and found to have an initial setting time of 24 min, a final setting time of 37 min, a flowability of 220 mm, a 2-hour flexural strength of 2.7 MPa, a 2-hour compressive strength of 14.2 MPa, a 28-day flexural strength of 7.4 MPa, a 28-day compressive strength of 42.8 MPa, a bond strength of 1.9 MPa, a water resistance coefficient of 0.86, and a permeability coefficient of 7.5 × 10⁻⁶. -12 m / s.

[0049] Comparative Example 7 The difference from Example 1 is that 0.05 parts of silane coupling agent are added, and waterborne polyurethane is not added; during preparation, the silane coupling agent and water are added to the dry mixture to form an inorganic slurry, and organic slurry 2 is not prepared. The remaining components, dosages and preparation methods are the same as in Example 1.

[0050] The comparative example was tested and found to have an initial setting time of 25 min, a final setting time of 39 min, a flowability of 218 mm, a 2-hour flexural strength of 2.3 MPa, a 2-hour compressive strength of 12.0 MPa, a 28-day flexural strength of 6.2 MPa, a 28-day compressive strength of 40.8 MPa, a bond strength of 1.4 MPa, a water resistance coefficient of 0.82, and a permeability coefficient of 9.8 × 10⁻⁶. -12 m / s.

[0051] Comparative Example 8 The difference from Example 1 is that the stepwise preparation process of inorganic slurry 1 and organic slurry 2 is not used. Instead, the gold tailings powder activated at high temperature, cement, slag, metakaolin, nano silica, quartz sand, water-reducing agent, coagulant, silane coupling agent, waterborne polyurethane, PVA fiber and water are mixed and stirred at one time. The stirring conditions are: first stirring at a low speed of 150 r / min for 30 s, and then stirring at a high speed of 400 r / min for 5 min. The remaining components and dosages are the same as in Example 1.

[0052] Testing revealed slight localized polymer agglomeration and a small amount of uneven fiber dispersion in the slurry of this comparative example. The initial setting time was 24 min, the final setting time was 39 min, the fluidity was 195 mm, the 2-hour flexural strength was 2.8 MPa, the 2-hour compressive strength was 14.8 MPa, the 28-day flexural strength was 7.6 MPa, the 28-day compressive strength was 39.5 MPa, the bond strength was 1.9 MPa, the water resistance coefficient was 0.84, and the permeability coefficient was 8.5 × 10⁻⁶. -12 m / s.

[0053] Comparative Example 9 The difference from Example 1 is that slag and metakaolin are not added, and 15 parts of slag and 9 parts of metakaolin are replaced by 24 parts of rapid-hardening sulfoaluminate cement to keep the total amount of cementitious materials consistent; the remaining components, dosages and preparation methods are the same as in Example 1.

[0054] The comparative example was tested and found to have an initial setting time of 16 min, a final setting time of 27 min, a flowability of 200 mm, a 2-hour flexural strength of 4.0 MPa, a 2-hour compressive strength of 23.5 MPa, a 28-day flexural strength of 8.1 MPa, a 28-day compressive strength of 41.6 MPa, a bond strength of 2.4 MPa, a water resistance coefficient of 0.86, and a permeability coefficient of 7.2 × 10⁻⁶. -12 m / s.

[0055] In summary, this invention successfully constructs an organic-inorganic composite repair material system that combines rapid setting, high strength and toughness, strong interfacial adhesion, and excellent impermeability and durability through the synergistic effect of rapid-hardening sulfoaluminate cement, high-temperature activated gold tailings, multi-mineral admixtures, nano-silica, and a waterborne polyurethane-silane coupling agent composite system. This material not only meets the timeliness requirements of rapid tunnel repair projects but also effectively improves the long-term service stability of the repair layer, demonstrating high engineering application value and significance for the resource utilization of industrial solid waste.

[0056] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A water-based polymer mortar for rapid repair of tunnel defects, characterized in that, include: 35-60 parts of gold tailings powder that has undergone ball milling and high-temperature activation treatment; 20-35 parts of rapid-hardening sulfoaluminate cement; 10-20 parts slag; 5-15 parts metakaolin; 0.5-2 parts nano-silica; the amount of waterborne polyurethane emulsion is 3%-8% of the mass of cementitious materials based on the total mass of the emulsion; 0.5%-1.5% of the mass of waterborne polyurethane; 0.2%-0.5% of the mass of cementitious materials; 0.05%-0.2% of the mass of cementitious materials; 80-150 parts quartz sand; 0.3% of the mass of cementitious materials; the amount of water used makes the water-cement ratio of the slurry 0.35-0.

45. The cementitious material is a combination of gold tailings powder, rapid hardening sulfoaluminate cement, slag, metakaolin and nano-silica. The specific surface area of ​​the gold tailings powder is ≥600 m². 2 / kg, D 50 ≤8 μm, SiO2 content ≥65%; The gold tailings powder with high-temperature activation treatment is obtained by ball milling, sieving and classifying gold tailings, and high-temperature calcination activation treatment. The heating rate of the high-temperature calcination is 5℃ / min, the high-temperature calcination temperature is 650℃, the holding time is 2h, and the powder is cooled to room temperature with the furnace after calcination.

2. The water-based polymer mortar for rapid repair of tunnel defects according to claim 1, characterized in that, The metakaolin is a highly active metakaolin, which is calcined at 600~900℃.

3. The water-based polymer mortar for rapid repair of tunnel defects according to claim 1, characterized in that, The nano-silica has an average particle size of 10-50 nm and a specific surface area of ​​100-300 m². 2 / g.

4. The water-based polymer mortar for rapid repair of tunnel defects according to claim 1, characterized in that... The waterborne polyurethane is an anionic waterborne polyurethane emulsion with a solid content of 40%~50% and a viscosity of 50~300 mPa·s.

5. The water-based polymer mortar for rapid repair of tunnel defects according to claim 1, characterized in that... The silane coupling agent is an aminosilane coupling agent and / or an epoxysilane coupling agent.

6. The water-based polymer mortar for rapid repair of tunnel defects according to claim 1, characterized in that... The water-reducing agent is a polycarboxylate-based high-performance water-reducing agent with a water reduction rate of ≥25%.

7. The water-based polymer mortar for rapid repair of tunnel defects according to claim 1, characterized in that... The fiber is PVA fiber or polypropylene fiber; the quartz sand is 70~120 mesh graded quartz sand.

8. The water-based polymer mortar for rapid repair of tunnel defects according to claim 1, characterized in that... The coagulant is at least one of inorganic lithium salt, inorganic sodium salt, and organic alcohol amine coagulant.

9. The method for preparing the water-based polymer mortar for rapid repair of tunnel defects according to any one of claims 1 to 8, characterized in that, Includes the following steps: S1. The gold tailings are ball-milled, screened and classified, and then subjected to high-temperature calcination activation treatment to obtain high-temperature activated gold tailings powder. S2. The gold tailings powder, rapid hardening sulfoaluminate cement, slag, metakaolin, nano silica, quartz sand, water-reducing agent and accelerator treated at high temperature are dry-mixed in proportion to disperse them evenly to obtain a dry mixture. S3. Add a portion of the silane coupling agent and water to the dry mixture and stir to form a uniform inorganic slurry 1. S4. Mix the waterborne polyurethane with the remaining silane coupling agent and stir until homogeneous to form a uniform organic slurry 2. S5. Add the organic slurry 2 to the inorganic slurry 1 and mix them evenly under high-speed stirring to form an organic-inorganic composite mortar. S6. Add the fiber to the organic-inorganic composite mortar and disperse the fiber evenly under low-speed stirring to obtain the water-based polymer mortar for rapid repair of tunnel defects.

10. The application of the water-based polymer mortar for rapid repair of tunnel defects as described in any one of claims 1 to 8 in tunnel defect repair projects.